2019
DOI: 10.1503/cjs.010718
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute care surgery on timeliness of care and patient outcomes: a systematic review of the literature

Abstract: Background: Dedicated emergency general surgery (EGS) service models were developed to improve efficiency of care and patient outcomes. The degree to which the EGS model delivers these benefits is debated. We performed a systematic review of the literature to identify whether the EGS service model is associated with greater efficiency and improved outcomes compared to the traditional model. Methods:We searched MEDLINE, Embase, Scopus and Web of Science (Core Collection) databases from their earliest date of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…As outlined by a recent systematic review on the impact of the ACS model on timeliness of care and patient outcomes, a lack of standard metrics and the absence of a dedicated comprehensive EGS database limit the ability to monitor performance and identify areas for quality improvement. 21 Although the ACS model has been a beacon of hope for addressing these issues, attention must be paid to timely access to the operating room. Other groups have found that even afterhours operating confers increased risk to patients undergoing general and vascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined by a recent systematic review on the impact of the ACS model on timeliness of care and patient outcomes, a lack of standard metrics and the absence of a dedicated comprehensive EGS database limit the ability to monitor performance and identify areas for quality improvement. 21 Although the ACS model has been a beacon of hope for addressing these issues, attention must be paid to timely access to the operating room. Other groups have found that even afterhours operating confers increased risk to patients undergoing general and vascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The same surgeons were involved in the pre-ACS and R-ACS cohorts but the reduction in complications for AC might be explained by increased experience with laparoscopy during the study period or possibly by the conduct of these procedures at a tertiary teaching institution. Variation in study definitions and outcome measures for EGS conditions are common throughout the scientific literature [17]. This makes a direct comparison among study results challenging.…”
Section: Discussionmentioning
confidence: 99%
“…There are 13 ACS services in Canada with significant variation in organization and function [1,5]. The lack of standardization for ACS outcome measures and reporting makes comparisons among ACS services challenging [17-18]. Acute appendicitis (AA) and acute cholecystitis (AC) are the most common EGS diagnoses requiring admission [7], with standard, measurable points of care along the patient trajectory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Trauma and EGS patients treated at specialized trauma and newly established ACS centers have achieved superior clinical outcomes compared to patients treated in nonspecialized centers. [2][3][4][5] The COVID-19 pandemic has challenged health care systems and hospitals with an increased demand for both human and material resources and has presented a unique opportunity to test the performance of the ACS model during this nonsurgical catastrophic event. 6 During the COVID-19 surge in Boston from March to May 2020, the ACS service at an urban, tertiary, level I academic trauma center was assigned to continue coverage of all trauma, EGS, and SCC patients, with the added responsibility of taking care of critically ill nonsurgical patients including COVID-19 positive patients.…”
Section: Introductionmentioning
confidence: 99%